Volume-based thermodynamics of ionic liquids and molten salts: Surface tension and the Eötvös equation - Glasser, Leslie (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
The surface thermodynamics of ionic fluids (both ionic liquids and molten salts) are calculated from surface tension data by application of a modified Eötvös Equation, and the results compared with the corresponding values for neutral organic liquids. As may be anticipated and here reported quantitatively, the coulombic interactions within the ionic fluids lead to smaller surface entropies and larger surface enthalpies because of tighter binding among the charged ions. For ionic liquids, an increase in formula volume leads to their surface properties tending towards those of neutral organic liquids, corresponding to a decrease in the strength of the coulombic interactions. Unexpectedly large surface entropies for molten GaCl3, BiBr3, BiCl3 and UF6 suggest that these species may be behaving as freely-spinning pseudo-spherical molecules.